(3GdcGeds - (3eMeO Hf jRjO Hf YHO GdCcHQ GdKeGdj GdCROj, GdeHQO , CHh GdYHGS,J (B286 (3g` s
(3ChdgG (B:s
(3HGH ef CNHGQ GdNhGQL bGd CHh GdYHGS PcQ Cgd GdYde ef GdUaQjI Cf GdNhGQL deG YRehG Ydi GdHjYI dYHO Gddg Hf OgH GdQGSHi ef GdCROJcQg Pdc s
(3BNQgG (B:s
(3hai GdbQBf (B" (3jNQLhG GdQShd hEjGce Cf JDefhG HGddg (B" (3aGdhba jNQLhf GdQShd hEjGce Ci (B: (3hjNQLhfce dCf JDefhG HGddg QHce Je GdcJGH GdcGed s
(3GdfSNI HgG MhGTs
(3HChdgG bQGAI SfI (B421s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B144 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B114s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdeMehOjI (B- (3HecJHI GdeOjfI GdefhQI GdYGeI (B((3dZI (B15) s
Keywords: (3GdCOHs